Keluarga Patriarki dalam Pandangan Feminisme Liberal: Studi Pada Keluarga di Desa Sumbertumpuk Pasuruan - Jasmiarto, Dicky; Ridwan, Ahmad; Listyani, Refti Handini (Jurnal Wanita dan Keluarga, 2025)
Patriarchal families are still the main pattern in the social structure of Sumbertumpuk Village, Pasuruan, which creates gender inequality and positions women in a subordinate position. This research aims to explore the dynamics of women's roles in patriarchal families and examine the views of liberal feminism as the basis for the transformation of gender equality in the neighborhood. This research method is qualitative research using a gender-based critical descriptive approach, through observation and in-depth interviews with women and men in the family. The results show that women in Sumbertumpuk face a double burden and limited access to education and economic opportunities, which strengthens their dependence on men. However, awareness of the need for change is starting to show through solidarity and small discussions within the family, as well as support from policies that favor women's empowerment. These findings emphasize the importance of policies and education that can facilitate a paradigm shift from patriarchal structures towards more egalitarian families, as supported by the philosophy of liberal feminism.